Study on the characteristics of atomic hydrogen cleaning carbon contamination on multilayers - Song, Yuan; Lu, Qipeng; Gong, Xuepeng; Wang, Dazhuang; Zhang, Zhen; Yu, Bo; Yao, Shun; Mao, Qijun; Ma, Tianyu; Bai, Yang (Vacuum, 2022)
Mo/Si multilayers are widely used in synchrotron radiation beam-lines and extreme ultraviolet lithography machines. With the increasing power of light source, the problem of carboncontamination on multilayers becomes more and more serious. In-situ efficient and non-damage removal of carbon contamination becomes very necessary. Atomic hydrogen has been proved an effective particle to cleaning carbon without damage. However, the mechanism of atomic hydrogen cleaning carbon contamination is not completely understood now and the cleaning rate is slowly. In order to realize efficient and in situ cleaning of carbon contamination by atomic hydrogen, the influence of different conditions on the process of atomic hydrogen cleaning carbon contamination was researched with experiment firstly. Then, the characteristic relationship of working distance, temperature and atomic hydrogen concentration on the cleaning rate was identified to study the mechanism. The cleaning rate could reach 0.0347 nm/min. In the end, the change of optical properties and surface roughness of multilayer after cleaning were analyzed. The result was shown that the reflectivity of the samples could be effectively recovered and the surface roughness of the samples had little change after cleaning. The workhas great significance for realizing the efficient atomic hydrogen cleaning carbon contamination in-situ. •The influence of different conditions on the process of H0 cleaning carbon contamination was researched by experiment.•The mechanism of cleaning was analyzed by the characteristic of d, T and H0 concentration on the cleaning rate.•The methods for increasing the cleaning rate were described based on mechanism and experiment.